The collected works of Samuel Taylor Coleridge. - Coleridge, Samuel Taylor, 1772-1834 (Bollingen series, 2015)
Published originally in 1809-1810, The Friend was revised in 1812, by public demand. In 1818, a three-volume rifacimento appeared in which Coleridge attempted to dispel obscurity, tie up loose threads of reasoning, and provide more mature apercus. Now, in the Collected Works, The Friend has been re-edited to return to Coleridge's 1818 text. His emendations, cuts, and marginal comments noted in six copies of the work, as well as manuscript additions and deletions, have been included as footnotes. The editor's footnotes also elucidate sources and themes and provide translations of the many Latin and Greek passages. The entire periodical Friend is given as an appendix, with the 1812 revisions. Originally published in 1969. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.